ANALISIS KINERJA KEUANGAN PT. MAHAKA MEDIA Tbk - -, Asnan Supian (EKONOMIA, 2014)
PT. Mahaka Media Tbk established in Jakarta under the name PT. Abdi Bangsa Tbk. On November 28, 1992 with No Deed. 229, later amended by Deed. 157 dated December 17, 1992. PT. Mahaka Media with taqline â€œuntimitedvcontent creationâ€ , is a multiplatform media company that makes, sells, collect and distribute content â€“ all community content through platforms that consumers need. The Company is located in the plaza ASIA (formerly plaza ABDA) 26th floor, Jalan Gen. Sudirman kav. 59, Jakarta 12190.The issues raised, is financial PT. Mahaka Media Tbk has increased in 2012 compared to 2011 and in 2010. In term of profitability ratio(profibility ratio) and growth ratio (growth ratio). The purpose and usefulness of this research is to investage the financial performance PT. Mahaka Media Tbk and provide a view of the theory to the leadership of the PT. Mahaka Media Tbk as suppoting the decision maker.Research data analysis is used as the income statement in 2010, in 2011 and 2012 and the balance of 2010, 2011 and 2012. Analytical method used is to use a profitability ratio that consists of gross profit margin increased in 2012 by 51.20% compared to the year 2011 was 46.49% and in 2010 amounted to 43.59%, return on assets (ROA) increased in 2012 by 1.31% compared to the year 2011 of 1.13% and 0.64 in 2010, return on equity (ROE) increased in 2012 by 1.07% compared to 0.78% in 2011 and 2010 amounted to 0.54%. The ratio of the growth which consists of the increase in sales (sales) decreased in 2012 by 6.60% compared to the year 2011 was 39.59% and the net profit (earning after tax0 in 2012 decreased by 42.99% compared to the year 2011 was 53.68%.Based on the analysis and discussion, it can be seen from the ratio of profitability which consists of Groos pofit margin, return on assets (ROA) and return on equity (ROE) visits from sales, gross profit, EBIT, EAT and total assets increased significantly. Consisting of growth ratio of the increase in sales (sales) and net profit (earning after tax) from the sale and EAT seen increased but not significantly.